FAKTOR - FAKTOR YANG MEMPENGARUHI KEKERASAN PADA ANAK DISABILITAS TERHADAP KASUS KEKERASAN PADA ANAK SESUAI PROGRAM FUNGSI PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT DI BUKITTINGGI - Astuti, Yeni; Yulihasri, Yulihasri; Amelia, Dona (Jurnal Ilmiah Ilmu Manajemen, 2020)
Children are the next generation of the nation who play a strategic role and have specal characteristics, so that guidance and protection is needed to ensure their growth and physical, mental and social development and development. Indonesian children aged 1-14 years experience violent discipline. This data is also strengthened from data from the Child Protection Commission (KPAI) which recorded that during 2019 there were 4369 public complaints received, and if we look at the case trends yearly, complaints about KPAI cases have increased in 2020 with a range of 4734. The PATBM program includes parents, family factors, and customs factors. The type of research to be used is this type of research is a type of Structral Equation Modeling research using SEM (Structural Equation Modeling) data analysis techniques based on Smart PLS variance. The results of this study indicate that partially the economic and knowledge variables have a positive and significant effect on the case of violence in children with disabilities, while parenting patterns and social facts have no positive and insignificant effect on the case of violence against children with disabilities. For this reason, it is recommended that the local government, the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3APPKB),the Public, the business world be able to make efforts to prevent and handle violence against women and children.